Una mirada a las dimensiones de la sostenibilidad empresarial - Chaihuaque, Bruno (2019)
Corporate Sustainability is a concept that has taken strength in the academic and professional fields for decades. Nonetheless, its use has not been without difficulties due to its multiple definitions. For this reason, this academic note aims to discuss on this concept, by contrasting its multiple definitions. In the same vein, the environmental, social and economic dimensions are addressed, according to the Triple Bottom Line Model proposed by John Elkington in the early 1990s and some scopes are shown regarding their incorporation on companies.